Neural and Genetic Correlates of the Social Sharing of Happiness - Matsunaga, Masahiro; Kawamichi, Hiroaki; Umemura, Tomohiro; Hori, Reiko; Shibata, Eiji; Kobayashi, Fumio; Suzuki, Kohta; Ishii, Keiko; Ohtsubo, Yohsuke; Noguchi, Yasuki; Ochi, Misaki; Yamasue, Hidenori; et al. (Frontiers in Neuroscience, 2017)
Happiness is regarded as one of the most fundamental human goals. Given recent reports that positive feelings are contagious (e.g., the presence of a happy person enhances others’ happiness) because of the human ability to empathize (i.e., sharing emotions), empathic ability may be a key factor in increasing one’s own subjective level of happiness. Based on previous studies indicating that a single nucleotide polymorphism in the serotonin 2A receptor gene (HTR2A rs6311 guanine (G) vs. adenine (A)) is associated with sensitivity to emotional stimuli and several mental disorders such as depression, we predicted that the polymorphism might be associated with the effect of sharing happiness. To elucidate the neural and genetic correlates of the effect of sharing happiness, we first performed functional magnetic resonance imaging (fMRI) during a “happy feelings” evocation task (emotional event imagination task), during which we manipulated the valence of the imagined event (positive, neutral, or negative), as well as the presence of a friend experiencing a positive-valence event (presence or absence). We recruited young adult women for this fMRI study because empathic ability may be higher in women than in men. Participants felt happier (p < 0.01) and the mentalizing/theory-of-mind network, which spans the medial prefrontal cortex, temporoparietal junction, temporal poles, and precuneus, was significantly more active (p < 0.05) in the presence condition than in the absence condition regardless of event valence. Moreover, participants with the GG (p < 0.01) and AG (p < 0.05) genotypes of HTR2A experienced happier feelings as well as greater activation of a part of the mentalizing/theory-of-mind network (p < 0.05) during empathy for happiness (neutral/presence condition) than those with the AA genotype. In a follow-up study with a vignette-based questionnaire conducted in a relatively large sample, male and female participants were presented with the same imagined events wherein their valence and the presence of a friend were manipulated. Results showed genetic differences in happiness-related empathy regardless of sex (p < 0.05). Findings suggest that HTR2A polymorphisms are associated with the effect of sharing happiness by modulating the activity of the mentalizing/theory-of-mind network.